Systematic Review on Indonesia Halal Certification - Ikhwan, Ihsanul (Ekonomi Islam Indonesia, 2024)
The implementation of the law mandates the establishment of a new government agency under the Ministry of Religious Affairs, namely the Halal Product Guarantee Agency (BPJPH), which was previously handled by LPPOM MUI. Halal certification aims to serve the interests of Muslims and support them in practicing their religious teachings. This study aims to examine the development of research on “Halal certification in Indonesia” published by journals on this topic. The data used are secondary data obtained from scientific publications indexed by the Scopus database of 106 documents. This research uses a qualitative method with a bibliometric approach, which is processed using VOSviewer software. The results of the study show that there are 4 research clusters including halal certification system in indonesia, consumer perceptions and halal certification in indonesia, halal cosmetics and halal certification in indonesia, implementation of halal standards and halal certification in indonesia.